PROPLAN - Sistema Computacional para o Planejamento da Protonterapia em Tumores Oculares - Marilia Tavares Christovao (2010)
This thesis presents a set of computational modules to assist proton radiotherapy planning in malignant ocular diseases, called PROPLAN - Computer System Planning for Proton Therapy in Ocular Tumors, in order to optimize and support decision making between radiotherapeutic procedures or treatment plans, according open source software principles. The software PROPLAN is a tool for optimizing and customizing treatment plans applied to ocular proton therapy. PROPLAN provides a graphical interface designed from code Geant4 (Geometry and Tracking Toolkit), which parameters of the planning are configured, providing data from an actual experiment installation in operation, consisting of its main elements, which applies a proton beam to control eye diseases. PROPLAN was designed and implemented by integrated modules in which the G4SISCODES is a conversion module that performs conversions of the output files from Geant4 code to the Computer System for Dosimetry in Radiotherapy - SISCODES. The operation module integrates the Geant4 libraries, from the application "Hadrontherapy", to the SISCODES. The Geant4 output information were adapted to the eye voxel model provided generated by the SISCODES system. The dose spatial distribution was reproduced by isodose curves. In this computing environment, simulations were performed, resulting in deep dose profiles and the spatial distribution for ocular proton radiotherapy protocols. Other computer simulations are presented, applying physical processes and distinct accessories configurations, used in clinical applications, like as: absorbing material or range shifter, modulation system and beam collimator. The results are presented as graphs and dose spatial distribution, involving modulated Bragg peak and isodoses. The PROPLAN proved to be a useful tool in planning for ocular proton beam radiation therapy. Such investigations are motivated the introduction of this treatment technique in the country.